SYSTEMATIC LITERATURE REVIEW : IMPLEMENTASI FORWARD CHAINING PADA SISTEM PAKAR ANALISIS KEPRIBADIAN SISWA - Saputra Aimi; Andrian; Yuanita Erfina; Rosyani Perani; Al Azhar Syukron (Journal of Research and Publication Innovation, 2023)
A health discipline called psychology looks at a person's (human) behavior or personality. One of the numerous things a person can do to determine the sort of personality he or she has is to speak with a psychologist. This is obviously a waste of time because it is highly expensive to contact a psychologist to learn more about your personality. A strategy that can solve the issue more quickly and effectively is thus required. With a dynamic knowledge base of dynamic knowledge, this expert system for student personality recognition was created as a tool for identifying students' personalities. To improve system performance while drawing conclusions, the knowledge base is set up in a database with a number of tables, including student tables, evaluation tables, and user tables. With data gathered from relevant journals between 2019 and 2023, this study seeks to assess the expert system for analyzing student personality using a transition sequence model. The systematic literature review (SLR) method was applied by the researchers in this study. One of the research methods used to systematically gather, assess, and synthesize data from numerous pertinent scientific articles or publications is called systematic literature review (SLR). Produce more results that are accountable and objective. Using pre-established techniques, this strategy looks for and picks pertinent materials. The database connected to the Expert System in Analyzing Student Personality Using the Forward Chaining Model is where the article search is related.